Faecal microbiota and short-chain fatty acid levels in faeces from infants with cow's milk protein allergy - Thompson-Chagoyan, O.; Fallani, M.; Maldonado, J.; Vieites, J.; Khanna, S.; Edwards, Christine; Doré, J.; Gil, A. (2011)
Background: The present study was designed to compare the faecal microbiota and concentrations of faecal short-chain fatty acid and ammonia between healthy and cow's milk protein allergic (CMPA) infants. Methods: The population comprised 92 infants aged 2-12 months who were nonallergic (n = 46) or diagnosed as having CMPA (n = 46). Faecal samples were analyzed by fluorescent in situ hybridization and flow cytometry, using a panel of 10 rRNA targeted group- and species-specific oligonucleotide probes. Acetic, propionic, butyric, isocaproic and branched-chain short fatty acids (BCSFA) were measured by gas-liquid chromatography, lactate by enzymatic reaction, and pH and ammonia levels were determined. Results: CMPA infant faeces had significantly higher proportions of the Clostridium coccoides group and Atopobium cluster and a higher sum of the proportions of the different bacterial groups in comparison to healthy infant faeces. Faecal pH and ammonia did not significantly differ between CMPA and healthy infants. Faeces concentrations and percentages of butyric acid and BCSFA were higher in CMPA infants than in healthy infants. Conclusions: The findings clearly set a link between a dysbiosis in gut microbiota composition and the pathogenesis of CMPA. No single species or genus appeared to play an essential role, but dysbiosis led to biomarkers of CMPA among bacterial fermentation products. Copyright © 2011 S. Karger AG, Basel.